Pengaruh Pelatihan dan Lingkungan Kerja terhadap Kinerja Karyawan - Yosef Ferry Pratama; Dian Wismar’ein (Business Management Analysis Journal (BMAJ), 2018)
This research departs from the existence of a research gap that discusses the effect of training and the work environment on employee performance. The inconsistency of the results of research and the existence of phenomena that occur in the company. In this study, the sample used amounted to 55 respondents with data collection methods using a questionnaire. The sampling technique in this study used proportional random sampling by processing data using SPSS. Independent variables in this study are work environment and job training. Based on the results of the data obtained the results that the job training variables and work environment have a positive and significant effect on employee performance.